STUDI FENOMENOLOGI PENGALAMAN KOPING REMAJA YANG MEMILIKI SAUDARA KANDUNG DENGAN AUTISME DI SEKOLAH LUAR BIASA KOTA PADANG - Rahmi Dwi Yanti (Universitas Baiturrahim, 2017)
Background: The presence of autistic children in a family will affect the lives of all other family members, including siblings. The response generated in adolescents due to their sibling who has autism has positive and negative implications, adolescents who are not able to solve problems and adapt to existing circumstances he would deal with stress. This study aimed to get an idea of the experience of coping teens who have siblings with autism. Methods: Qualitative research design using the phenomenological approach, the data collection process transactions are carried out through in-depth Interview. Participants were taken by purposive sampling. Participants in this study amounted to 7 adolescents. Analysis of the data by the method Colaizzi. Results: The results of this study resulted in 5 themes: an emotional response, adolescent perception of the sibling with autism, adolescent coping mechanisms, coping resources, and expectations of adolescents on the autism brother. It is expected to nurse the soul, the awareness of the importance of attention to aspects of emotional response in adolescents who have siblings with autism.